Problem of Migrant Children in the Mathematics Classroom - Parajuli, Kharika Devi (Journal of Mathematics Education, 2023)
The main purpose of this paper was to explore the key problems faced by migrant children in learning mathematics in the new classroom setting. For exploring this issue, I used a qualitative research method in which I conducted in-depth interviews with a few migrant children from the marginalized community. I analyzed the information to construct themes by connecting students generated text with their experience. The finding of the study included three themes: adjustment difficulties, language barriers, and cultural devaluation. These findings may be useful to school students, teachers, and mathematics educators to foster multiple opportunities to develop respect for various cultural learning environments for students’ success in school and the classroom.